X-ray photoelectron spectra and electronic structure of quasi-one-dimensional SbSeI crystals - Grigas, J.; Talik, E.; Adamiec, M.; Lazauskas, V. (Condensed Matter Physics, 2007)
The paper presents the X-ray photoelectron spectra (XPS) of the valence band (VB) and of the principal core levels from the (110) and (001) crystal surfaces for the quasi-one-dimensional high permittivity SbSeI single crystal isostructural to ferroelectric SbSI. The XPS were measured with monochromatized Al Ka radiation in the energy range of 0–1400 eV at room temperature. The VB is located from 1.6 to 20 eV below the Fermi level. Experimental energies of the VB and core levels are compared with the results of theoretical ab initio calculations of the molecular model of the SbSeI crystal. The electronic structure of the VB is revealed. Shifts in the core-level binding energies of surface atoms relative to bulk ones, which show a dependency on surface crystallography, have been observed. The chemical shifts of the core levels (CL) in the SbSeI crystal for the Sb, I and Se states are obtained. Дана стаття представляє рентгенiвськi фотоелектроннi спектри (РФС) валентної зони (ВЗ) i остовних рiвнiв кристалiчних поверхонь (110) i (001) квазiодновимiрного монокристалу SbSeI з високою проникливiстю, який iзоструктурний сегнетоелектрику SbSI. РФС вимiряно з використанням монохроматичного випромiнювання Al K в енергетичному дiапазонi 0–1400 еВ при кiмнатнiй температурi. ВЗ розташована вiд 1.6 до 20 еВ нижче рiвня Фермi. Експериментальнi енергiї ВЗ та остовних рiвнiв порiвняно з результатами теоретичних розрахункiв “з перших принципiв” для молекулярної моделi кристалу SbSeI. Встановлено електронну структуру ВЗ. Виявлено зсуви остовних енергiй зв’язку поверхневих атомiв вiдносно об’ємних, якi демонструють залежнiсть вiд кристалографiї поверхнi. Отримано хiмiчнi зсуви остовних рiвнiв у кристалi SbSeI для Sb, Se та I.